Exploring English Vocabulary Mastery in Student with ASD at Upper Primary School Level : Case Study of Multisensory Approach Implementation - Sambas, Ela Carmelia Mukti; Emeliyah Sukma Dara (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines how multisensory approach is implemented so that this approach have effects on the learning for elementary school students with ASD (Autism Spectrum Disorder) especially in mastering vocabulary. The research is rooted in the difficulties ASD student encounter in vocabulary mastery, especially concerning sensory information processing and understanding language. The methodology employed in qualitative, using case study with data collected through observations and interviews with shadow teacher and homeroom teacher. The findings indicate that the implementation of methods involving various sensor modalities—visual, auditory, kinesthetic, and tactile—significantly aids student in understanding word meanings, using them in appropriate context, and strengthening their memory skills. The conclusion of this research emphasize that personalized and context-rich approaches can provide the necessary support for language development in student with ASD. Therefore, it is crucial for educators to apply relevant and adaptive methods in inclusive education.